Tetracera scandens as a Medicinal Plant: Secretory Structures, Histochemistry, and Antibacterial Activity - Evi Muliyah; Sulistijorini Sulistijorini; Yohana Cecilia Sulistyaningsih; Mohamad Rafi (Journal of Tropical Life Science, 2018)
Tetrascera scandens, a member of Dilleniaceae, is used for traditional medicine; the stem is utilized by the Anak Dalam tribe of Jambi Province, Sumatera island, Indonesia, to treat diarrhea symptoms. The aims of this study were to identify the secretory structures, histochemical aspects, and the antibacterial potency of T. scandens stem. Histological study of the secretory structures of T. scandens stem was carried out. The species has idioblast cells and trichomes as its secretory structures. Histochemical analysis indicated the substance secreted by T. scandens idioblast cells mainly contains alkaloids, terpenoids, and phenols. Trichomes of T. scandens only contain flavonoids. The antibacterial activity of methanol extracts was tested against Staphyllococcus aureus and Escherichia coli. Different concentration of extracts was tested using the well diffusion method. According to the results, 100 mg/mL T. scandens extract showed the best inhibitory activity with a maximum inhibition zone of 17.7 mm against S. aureus and of 12.5 mm against E. coli. This study provides scientiï¬c evidence that the stem of T. scandens has antibacterial activity and justiï¬es its use by the local community.